(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
The policy of beach reclamation on Boulevard Manado which is quite extensive has caused some problems or incompatibilities in terms of the socio-economic conditions of fishing communities around the reclamation area. After the coastal reclamation policy was implemented it turned out to have an impact on the surrounding fishing community who had difficulty in finding fish and meeting their needs. So in getting the formulation of the problem of how the socio-economic impacts felt by the fishing community due to the policy of coastal reclamation on Boulevard Manado, especially in Sario District. The purpose of this research is to provide an overview and analyze the socio-economic impacts felt by fishing communities as an impact arising from the policy of coastal reclamation on Boulevard Manado. This research was conducted to evaluate the impact of the coastal reclamation policy. In evaluating the impact of this policy, the researcher used the theory of impact evaluation or summative evaluation with the eveluation method of Rossi and Freeman, then used the Act and a number of other advocate theories. This type of research is descriptive with a qualitative approach. Keywords: Policy, Coastal Reclamation, Impact.